EVALUASI PENERAPAN HIGIENE DAN SANITASIPENYELENGGARAAN MAKANAN DI RSUD SUNANKALIJAGA KABUPATEN DEMAKTAHUN 2013 (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
Food sanitary is very important especially at the public service places such as hospital. In supporting medical service for patients, it’s better to maintain best food processing according to the food’s hygiene and sanitary standard. Therefore, this research was aimed to find out the representation of sanitary hygiene description of food processor at RSUD SunanKalijagaDemak.It was descriptive research with evaluation-based approach. This research focused on describing the hygiene and behavior of food processor during the food processing at NutritionsInstalation of RSUD SunanKalijagaDemak.The research showed that evaluation about physical worthiness for sanitary hygiene of the food was still under the minimal score, it was 80. While evaluation using inquiry form indicated that the irrelevancy happened could be categorized into small irrelevancy, which was in 81% level. Nevertheless, the food processor hygiene practice was good enough.Some suggestion from the researcher, there should be more periodically knowledge development and improvement about food sanitary hygiene for food processor, improvement in supervisory of food service process, and also applying food sanitary hygiene in the food processing.